TiRobot ForcePro Superior combined with suture-button plates for minimally invasive treatment of an acetabular both-column fracture - a case report - Dai Yonghong; Zeng Yanhui (BMC Musculoskeletal Disorders)
Abstract Background The acetabulum exhibits an irregular anatomical structure with a dense concentration of critical blood vessels and nerves in its vicinity. Acetabular fractures accompanied by periarticular soft tissue injuries may lead to life-threatening complications. The Letournel-Judet classification system is currently the widely adopted standard for categorizing acetabular fractures, with the both-column fracture type recognized as the most complex pattern within this framework. Open reduction and internal fixation remains the gold standard for its management. The minimally invasive closed reduction of acetabular both-column fractures with significant displacement remains an unresolved global challenge in orthopedic surgery. Our surgical team has developed an innovative approach that provides a novel solution to this complex clinical problem. Therefore, this article was compiled to provide a comprehensive description of this surgical technique, thereby offering novel insights for the orthopedic surgeons. Case presentation A 33-year-old male patient sustained a left-sided acetabular both-column fracture due to a high-altitude fall. Under the guidance of the TiRobot ForcePro Superior, we first established a bony channel, then passed a suture-button plate through the quadrilateral plate of the acetabulum. Subsequently, high-strength sutures were tightened using a suture tensioner to achieve compression reduction of the fracture fragments. Following reduction, screws were inserted with robotic assistance via the TiRobot ForcePro Superior to achieve rigid fixation of the fracture site. The patient underwent an 11-month follow-up. Radiographic evidence of bony consolidation was confirmed at the 4th postoperative month, with no traumatic arthritis observed throughout the follow-up period. Pelvic function demonstrated excellent recovery, achieving a Majeed Pelvic Function Score of 92 points. There was virtually no difference in the patient’s function regarding sitting, walking, standing, and sexual activity compared to pre-injury, and no gait alteration was observed. Conclusions With the assistance of robot-aided surgery combined with suture-button plates, our surgical team successfully achieved minimally invasive closed reduction and internal fixation for an acetabular both-column fracture. This innovative surgical approach provides a novel strategy for the minimally invasive management of acetabular both-column fractures.